2019
DOI: 10.3390/genes10010051
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Comparison of the Relationship of Epigenetic Aging and Epigenetic Substance Consumption Markers to Mortality in the Framingham Heart Study

Abstract: A number of studies have examined the relationship of indices of epigenetic aging (EA) to key health outcomes. Unfortunately, our understanding of the relationship of EA to mortality and substance use-related health variables is unclear. In order to clarify these interpretations, we analyzed the relationship of the Levine EA index (LEA), as well as established epigenetic indices of cigarette (cg05575921) and alcohol consumption (cg04987734), to all-cause mortality in the Framingham Heart Study Offspring Cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 35 publications
(69 reference statements)
4
25
0
Order By: Relevance
“…This observation suggests that the methylation sites that are nominally associated with smoking are also associated with additional aspects of aging [15]. For example, methylation of one of the genes associated with this surrogate, cg05575921, which codes for aryl hydrocarbon receptor repressor (AHRR), is not solely a function of smoking, but also reflects exposure to various environmental exposures and xenobiotics, including polycyclic hydrocarbons, airborne particulate matter and certain pharmaceuticals [35]. Of potential importance, the aryl hydrocarbon receptor also plays important roles in inflammation, cell differentiation and cell cycle control [36].…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests that the methylation sites that are nominally associated with smoking are also associated with additional aspects of aging [15]. For example, methylation of one of the genes associated with this surrogate, cg05575921, which codes for aryl hydrocarbon receptor repressor (AHRR), is not solely a function of smoking, but also reflects exposure to various environmental exposures and xenobiotics, including polycyclic hydrocarbons, airborne particulate matter and certain pharmaceuticals [35]. Of potential importance, the aryl hydrocarbon receptor also plays important roles in inflammation, cell differentiation and cell cycle control [36].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, all analyses statistically controlled for participants’ annual income at age 29 and educational level at age 29, to control for potential effects of adult SES on health outcomes (see Cockerham, Hamby, & Oates, 2017; Minkler, Fuller-Thompson, & Guralnik, 2006). Similarly, all analyses controlled for sex (1 = male ), and health behaviors assessed at age 29 (including substance use, diet, and exercise) to control for factors in adulthood that might influence health outcomes (Beach et al, 2015; Mills et al, 2019; Rezende, Rodrigues Lopes, Rey-LĂłpez, Matsudo, & Luiz, 2014; Schwingshackl & Hoffmann, 2015). Items assessing level of substance use at age 29 included alcohol consumption (“How many alcoholic drinks have you consumed during the past month?”), cigarette use (“How many cigarettes have you smoked in the last 3 months?”), and marijuana use (“How many times have you used marijuana during the past month?”).…”
Section: Methodsmentioning
confidence: 99%
“…Such differences have the potential to yield scales that reflect different influences across racial/ethnic groups. For example, in the FHS (White) sample, the DNAm PhenoAge EA index largely loaded on cigarette and alcohol consumption and this was not the case in the FACHS (AA) sample [ 24 , 25 ]. Since the rate of smoking and alcohol consumption are roughly equal in Whites and AAs [ 38 , 39 ], it is unlikely that differences in habits affected the methylation outcomes, suggesting that the DNAm PhenoAge index is operating somewhat differently across ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…For example, with respect to smoking, we have shown that almost 90% of the top ranked CpG sites for predicting are affected by ethnic specific genetic variation [ 23 ]. In the Framingham Heart Study (FHS) Offspring Cohort, which consists of individuals of European ancestry, 195 of the 513 CpG sites in the DNAm PhenoAge EA Index are significantly associated with methylation at the well-established indicator of smoking, cg05575921 [ 24 ]. However, in AA samples, the Levine PhenoAge Index is only modestly associated with cotinine seropositivity and cg05575921 inferred smoking intensity [ 25 ].…”
Section: Introductionmentioning
confidence: 99%